Isotopic dating and geochemical characterization of petroleum system events: case studies from the McArthur, Tarim and Sichuan Basins - Li, Shaojie (Curtin University, 2019)
This PhD project has examined the behaviour and applicability of Re-Os and Rb-Sr isotope systems for dating and characterizing petroleum systems. Through case studies of ancient petroleum systems in the McArthur, Tarim and Sichuan Basins, outcomes of the project demonstrate that Re-Os source rock geochronology, Rb-Sr illitic clay and pyrite subsample geochronology can be used to dating hydrocarbon generation, charge and alteration, respectively, and Re-Os systematics are capable of differentiating and characterizing multiple hydrocarbon sources.